The genome of single-petal jasmine (Jasminum sambac) provides insights into heat stress tolerance and aroma compound biosynthesis - Qi, Xiangyu; Wang, Huadi; Chen, Shuangshuang; Feng, Jing; Chen, Huijie; Qin, Ziyi; Blilou, Ikram; Deng, Yanming (Frontiers in Plant Science, 2022)
Jasmine [Jasminum sambac (L.) Aiton] is a commercially important cultivated plant species known for its fragrant flowers used in the perfume industry, medicine and cosmetics. In the present study, we obtained a draft genome for the J. sambac cultivar ‘Danbanmoli’ (JSDB, a single-petal phenotype). We showed that the final genome of J. sambac was 520.80 Mb in size (contig N50 = 145.43 kb; scaffold N50 = 145.53 kb) and comprised 35,363 genes. Our analyses revealed that the J. sambac genome has undergone only an ancient whole-genome duplication (WGD) event. We estimated that the lineage that has given rise to J. sambac diverged from the lineage leading to Osmanthus fragrans and Olea europaea approximately 31.1 million years ago (Mya). On the basis of a combination of genomic and transcriptomic analyses, we identified 92 transcription factors (TFs) and 206 genes related to heat stress response. Base on a combination of genomic, transcriptomic and metabolomic analyses, a range of aroma compounds and genes involved in the benzenoid/phenylpropanoid and terpenoid biosynthesis pathways were identified. In the newly assembled J. sambac genome, we identified a total of 122 MYB, 122 bHLH and 69 WRKY genes. Our assembled J. sambac JSDB genome provides fundamental knowledge to study the molecular mechanism of heat stress tolerance, and improve jasmine flowers and dissect its fragrance.